Competing through cooperation: Standard setting in wireless telecommunications - Aija Leiponen (The Research Institute of the Finnish Economy (ETLA), 2006)
This study examines cooperative standard-setting in wireless telecommunications. Focusing on the competition among firms to influence formal standardization, the roles of standardsetting committees, private alliances, and technical consortia are highlighted. The empirical context is Third Generation Partnership Project (3GPP), an international standards development organization. Panel data analyses suggest that participation in external technical consortia significantly enhance firms' contributions to the development of new specifications in 3GPP committees. Then, once a firm has become a central player in technical committees, it can further influence the standard-setting outcome through change requests to ongoing specifications. External alliances with fellow 3GPP members may also improve change request success. These results suggest that if firms in network technological industries want to influence the evolution of their industry, they should identify both formal standard-setting committees and external cooperative arrangements in which they can discuss, negotiate, and align positions on technical features with their peers. For policymakers, these results suggest that it is important to ensure that technical consortia remain open for all industry actors and that membership fees do not become prohibitive to small and resource-constraint players.
Keywords: L15; L41; L96; O34; O38; 330; Standard setting; technology strategy; inter-firm networks; Funktechnik; Telekommunikation; Unternehmensnetzwerk; Normung; Welt